Tc-99m myocardial SPECT image quality improvement with a physical filter as scattered gamma photon absorber: phantom study - Sayed, Inayatullah Shah; Mohd Zulkele, Nurul Farizan; Che Daud, Mohd. Zamzuri; Abdul Rahim, Mohamad Shahrir (2017)
Introduction: Presence of scattered gamma photons in the projection data of Tc-99m Myocardial SPECT degrades the image quality. Thus, the efficacy of SPECT in patient studies is hampered. This work is aimed at enhancing the image quality and accuracy in measurement of cold defect size by pre-filtering of scattered gamma photons with physical filter. Material and method: GE Infinia II gamma camera with LEHR collimator was used. A flat sheet of Aluminum 0.1 mm thick, 55 cm x 44 cm sized was mounted on the outer surface of collimator. Carlson’s phantom with cardiac insert simulating the left ventricle was scanned. A polystyrene cold defect (9.8 mm x 9.8 mm x 9.8 mm) was placed at the anterior side of the myocardial wall. Water was filled into myocardial wall chamber; Tc-99m with concentration of 3.9μCi/ml was injected. It was inserted into the cylindrical tank after water was filled. Tc-99m radioactivity with 1.1μCi/ml concentration as background was administered. The chamber was positioned according to the orientation of human heart. Energy window (20%) centred at 140 keV was adjusted. Data were registered into a 128x128 matrix with sixty projections with and without physical filter opting step-and-shoot acquisition extended in a 180o arc from 45˚ right anterior oblique to 45˚ left posterior oblique. Filtered back projection method was used for image reconstruction by selecting Butterworth filter of order 10 and cut-off frequency 0.40/cm. Chang’s attenuation correction was applied. Results: Cold defect size measurement and image contour analysis of short axis views show significant improvement (p<0.05) in the accuracy in defect size and image quality with physical filter. Our study demonstrates that this technique is effective in removing scattered gamma photons from SPECT projection data. Conclusion: Physical filter technique may be implemented in Tc-99m myocardial SPECT clinical studies. Yet still, further studies are required with different phantoms which mimic the human heart closely.